(untitled) (Bangladesh Pharmaceutical Journal, 2015)
The crude methanol extracts of the bark and leaves of Syzygium fruticosum (Roxb.) DC. were partitioned with petroleum ether, carbon tetrachloride, chloroform and water for biological investigation. In the brine shrimp lethality bioassay, carbon tetrachloride soluble fraction of leaf extract (LCTF) showed significant lethality having the LC50 value 0.65 ?g/ml. In free radical scavenging activity screening (DPPH assay), chloroform fraction of methanolic extract of bark of S. fruticosum showed the highest free radical scavenging activity with IC50 value 20.01 ?g/ml. In the microbiological investigation, only chloroform soluble fraction of bark (BCF) and aqueous fraction of bark (BAF) showed mild antimicrobial activity with zone of inhibition ranging from 7 to 14 mm as compared to standard ciprofloxacin (zone of inhibition of 50 mm). In the study for thrombolytic property, different extracts of S. fruticosum revealed varying degrees of thrombolytic activity ranging from 33.46% to 62.51%. DOI: http://dx.doi.org/10.3329/bpj.v17i1.22315 Bangladesh Pharmaceutical Journal 17(1): 51-54, 2014